The importance of instrument traceability by the nursing team of the Surgical Center of a Hospital Universitário Federal do Rio de Janeiro/Brazil (Research, Society and Development, 2022)
Traceability of instruments brings security to professionals and clientele, whose care reveals to be part of the patient safety protocol, which is revealed as important by the nursing team. Objective: to analyze the importance of instrument traceability by the nursing team of the Surgical Center of a Hospital Universitário Federal do Rio de Janeiro/Brasil at the Centro Cirúrgico. Methodology: Field research, carried out at a Hospital Universitário Federal do Rio de Janeiro/Brasil at the Centro Cirúrgico, which was approved by the Research Ethics Committee of the Augusto Motta University Center, by CAAE 57253322.4.0000.5235 and the opinion number: 5,321,829, in which 52 nursing professionals answered a questionnaire on Google Forms. Result: Participants correctly answered the online form, which evidenced the important traceability for validation of the instrument, to be used in surgical procedures. Discussion: When analyzing the answers to the authors, it is clear that the traceability of the material, despite being important, requires an institutional investment and training for the entire team, being a medium and long-term process, but after implementation, it offers protection for the staff and clientele. Conclusion: The research evidences the result of the traceability of the sterilization process by the nursing professionals of the Surgical Center, for the use of instruments to minimize the risks in the clientele in the surgical procedure.